Clinical epidemiology of epithelial ovarian cancer in the UK - Doufekas K; Olaitan A (Dove Medical Press, 2014)
Konstantinos Doufekas, Adeola OlaitanDepartment of Gynaecological Oncology, University College London Hospitals, London, UKAbstract: Epithelial ovarian cancer is the fifth commonest cancer among women and the leading cause of gynecological cancer death in the UK. Most women present with advanced disease, mainly because the nonspecific nature of the symptoms lead to diagnostic delays. Recent data have shown a fall in ovarian cancer mortality rates in the UK, but rates are still higher when compared to other European countries or the USA. In addition, surgeons in the UK achieve on average lower optimal surgical cytoreduction rates in patients with advanced ovarian cancer. Despite a wealth of information on epidemiological risk factors, the pathogenesis of epithelial ovarian cancer remains largely unknown. This review presents the most recent data on incidence, mortality, and survival for epithelial ovarian cancer in the UK. Time trends, trends by age, international comparisons, and regional variation in incidence, survival, and mortality are presented within the context of a major reorganization of cancer services that took place in the UK over 10 years ago. Centralization of cancer services has meant that women with ovarian cancer receive treatment in specialist Cancer Centers.Keywords: ovarian, cancer, epidemiology, UK, incidence, survival